Analisis Pesan Moral dalam Music Video BTS “Life Goes On” (Kajian Semiotika Roland Barthes) - Siregar, Elsa Tabina; Ritonga, Muhammad Husni (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study aims to analyze the moral message contained in the music video "Life Goes On" from the music group BTS using Roland Barthes' semiotic approach. This music video was chosen because it presents a meaningful visual narrative that can be interpreted through the existing signs. This research uses descriptive analysis methods to identify signs that communicate moral messages, then analyzes the hidden meaning behind these signs. The main findings of this research reveal that the music video "Life Goes On" communicates a moral message about courage, hope and solidarity in facing difficult times. The results of the analysis also highlight the use of visual symbols that depict the power of friendship and togetherness in overcoming life's challenges. This research makes an important contribution to understanding how moral messages can be conveyed through visual media such as music videos, as well as the importance of semiotic studies in deciphering the meaning of hidden signs.
Keywords: Analysis; Moral Message; Music Video; BTS “Life Goes On; Semiotics Roland Barthes